Paradoxical vocal cord motion causing stridor after thyroidectomy. Issue 6 (1st June 2000) - Harbison, Joseph; Dodd, Jonathan; McNicholas, Walter T
Abstract : Two women developed stridor immediately after thyroidectomy as a result of paradoxical vocal cord motion. In both cases the cord function showed a normal pattern during vocalisation but paradoxical movement was seen at laryngoscopy during tidal breathing. The abnormality improved in both patients over time with speech therapy. Whilst the syndrome of paradoxical vocal cord motion is classically thought to have a largely psychological aetiology, subtle interference with laryngeal innervation at surgery is more likely to have been the cause in these cases.